Measurement of Thermooptic Coefficient in Lead Sulfide Using Laser Single-Beam Scanning Technique - Ban Bader; Oday Hamadi; K. Afnan (Engineering and Technology Journal, 2007)
In this work, the single beam scanning technique was employed to expressthe nonlinear interaction between laser radiation and semiconductor material(lead sulfide) as well as to determine the thermooptic coefficient of thematerial (lead sulfide). Direct measurement, low cost and reliability are themain features of this technique. The value of the thermooptic coefficient wasdetermined to be -5.8x10-5K-1 for PbS thin film. Due to authors review, this isthe first attempt in Iraq to measure such parameter in semiconductor thinfilms.